Problem Oriented Training in Emergency Medical Care Under the Conditions of Extremal Technogenic Situation (the Example of Solving a Situational Task) - V. I. Barklaya; V. Yu. Pikovsky; D. G. Kostomarov (Неотложная медицинская помощь)
The article provides a situational task with a detailed solution, reflecting the principles and procedure for the provision of emergency medical care outside a medical organization during a technogenic emergency (explosion followed by a fire) with several victims. This type of educational technology is applicable both during practical exercises with elements of simulation training, and monitoring the level of training of medical personnel.